Ijtihad Maqashidiy (Kontekstualisasi teori Maqashid Syariah di era Modern) - Andriyaldi Andriyaldi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
As we know, that the sacred religious texts (the Qur’an and the Sunnah of the Prophet SAW) was not able to answer the ‘direct’ contemporary issues that arise in the present age as the age of information and technology. Therefore, Islam as a religion of ‘rahmatan lil’ Alamin‘, must answer to cases that arise in many areas of life. In the study of Islamic jurisprudence, a tool to dig the law that does not exist it is “ijtihad”. However ijtihad needs to understand the purpose dialas with passion syar’iy so, Islam actually perceived as a religion that can give a solution every where and the conditions. The effort to find solutions using maqashid sharia law is called “ijtihad maqashidiy”. Through this ijtihad maqshidiy, it is expected to offer legal solutions that are right on target taking into account the conditions (al-waqi ‘) and the object is subject to legal load (mukallaf). To apply maqashidiy ijtihad in order to answer the contemporary issues, there are some devices (al-multazamat) that must be owned by a scholar or observer of Islamic law, namely: (1) understanding the texts or the language well, so that it can be understood ‘illat (reasonable) of a law. (2) understand the conditions under which an ijtihad results will be applied. (3) understand the condition of the object that is subjugated (mukallaf).